Evaluation of in-situ wind speed and wave height measurements against reanalysis data for the Greek Seas - Sifnioti, Dafni E.; Soukisian, Takvor S.; Poulos, Serafim E.; Nastos, Panagiotis T; Hatzaki, Maria (MEDITERRANEAN MARINE SCIENCE, 2017)
{ERA-Interim, ECMWF's reanalysis product, includes wave and atmospheric characteristics, with high temporal and spatial scale, providing more information on the marine state. Even though their assimilation process has been validated and verified in numerous studies, their performance in more local scales is still under examination. This research focuses on the evaluation of performance of ERA-Interim reanalysis datasets in the Greek Seas for wind and wave characteristics in comparison to POSEIDON buoy data. The results prove fair to good correlation for wave height (r=0.67-0.94) and wind speed (r=0.71-0.83) and different error statistics per sub-region. The analysis of the upper 10% (90th percentile) shows an underestimate of 10-15% for wind speed and wave height from ERA-Interim in relation to the buoy measurements. The ERA-Interim and the buoy monthly means and standard deviations are also presented and discussed according to seasonal patterns. The results of the study are compared to other researches of wave hindcasting and wind reanalysis data for the Greek Seas and globally. It is shown that ERA-Interim products could be regarded as representative for the Greek Seas, although their application should be made with caution regarding the assessment of extreme conditions (i.e. given in analyses of upper percentiles) and especially at nearshore locations due to complex coastline configuration enhanced by the great number of islands.}
Keywords: Aegean Sea; Ionian Sea; Poseidon Buoys; Wave and Wind Characteristics}; {ERA-Interim reanalysis products